Legal Implications for Children of Mixed Marriage and On Citizenship Rights in Indonesia - Taufik Hidayat; Hepy Krisman Laia; Ali Yusran Gea (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Mixed marriages between Indonesian Citizens (WNI) and Foreign Citizens (WNA) are increasing along with globalization. This phenomenon has significant legal implications, especially in the aspects of immigration and citizenship. Children born of mixed marriages (between Indonesian citizens and foreigners) have dual citizenship limited to the age of 18 years (or a maximum of 21 years). This is regulated in UU No. 12 of 2006 concerning Citizenship.Children automatically obtain Indonesian citizenship if one of their parents is an Indonesian citizen (principle of ius sanguinis). After 18 years, the child must choose one of the nationalities. If they do not choose on time, the child can become an apatride (without citizenship). The impact of mixed marriage poses problems including the Risk  of Apatride, the Risk  of Bipatride, Limited Inheritance Rights and Confusion in Legal Procedures.